2012
DOI: 10.1186/1471-2458-12-945
|View full text |Cite
|
Sign up to set email alerts
|

Men’s and women’s exposure and perpetration of partner violence: an epidemiological study from Sweden

Abstract: BackgroundOver the past 30 years, intimate partner violence (IPV) against women and its health consequences has become a well established research area and is recognized worldwide as a significant public health issue. Studies on IPV directed at men are less explored, however recently women’s use of IPV and men’s victimization is gaining growing attention. Earlier population-based studies performed in Sweden have primarily investigated men’s violence against women, while women’s use of violence and men’s exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 32 publications
11
82
2
2
Order By: Relevance
“…Recent studies have reported that sex-differences might be only found in lifetime victimization and perpetration estimates when compared to past year estimates, reflecting women's more severe experiences (Lovestad and Krantz 2012;Nybergh et al 2013). However, an analysis of lifetime prevalence for the four types of IPV assessed (Supplementary Tables 5, 6) revealed the same crosscountry differences as noted for past year estimates and sex-differences within each site also followed the same pattern found for past year estimates.…”
Section: Differences Between Sexesmentioning
confidence: 56%
See 2 more Smart Citations
“…Recent studies have reported that sex-differences might be only found in lifetime victimization and perpetration estimates when compared to past year estimates, reflecting women's more severe experiences (Lovestad and Krantz 2012;Nybergh et al 2013). However, an analysis of lifetime prevalence for the four types of IPV assessed (Supplementary Tables 5, 6) revealed the same crosscountry differences as noted for past year estimates and sex-differences within each site also followed the same pattern found for past year estimates.…”
Section: Differences Between Sexesmentioning
confidence: 56%
“…In the Swedish general population more past year sexual coercion victimization was also found in women [3.2 vs. 0.6 % with the use of the CTS2 (Lovestad and Krantz 2012) and 3.0 vs. 2.3 % with the WHO tool (Nybergh et al 2013)] while perpetration was declared by 5.2 % of men and 0.8 % of women. As with other self-reported sensitive and private issues, gender and country-specific stigma about IPV perpetration may impact on self-disclosure, although if this was the case, we would expect larger within-country differences than those noted.…”
Section: Differences Between Sexesmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, em contraste com outras formas de violência interpessoal, a violência por parceiro íntimo é muitas vezes perpetrada também por mulheres 7,15 .…”
Section: Discussionunclassified
“…O foco predominante da maioria dos estudos sobre violência por parceiro íntimo coloca a mulher como vítima e o parceiro masculino como agressor, desconsiderando que as mulheres também podem assumir o papel de agressoras 7 . A violência por parceiro íntimo quando associada à DST pode tornar a situação ainda mais complexa.…”
Section: Introductionunclassified